Fiscal Decentralization Policy in Promoting Indonesia Human Development - Soejoto, Ady; Subroto, Waspodo Tjipto; Suyanto, Y. (International Journal of Economics and Financial Issues, 2015)
Goal of this research is promoting human development in Indonesia through fiscal decentralization. In general, funds decentralization, economic growth, public expenditure, and a decline in total poor population in the autonomous region provide significant positive effect on human development index, thus increasing decentralization funds as balance grants to autonomous regions can be used to finance local expenditure, especially public social expenditure in education and health increased more years. Fiscal decentralization policy is instrumental in supporting the success of Indonesia's human development. In particular the research of fiscal decentralization policy yield in promoting human development as an economic overview of democracy in Indonesia counties and cities were assessed based on a review of theoretical and empirical can be concluded as follows: (1) Increased decentralization funds proven to provide significant positive effect on the amount of public expenditure. (2) Increased decentralization funds proved to have a positive effect on economic growth. (3) The increasing of total poor population in the autonomous region. (4) Regional economic growth is increased not provide significant effect on reducing total poor population. (5) Decentralized funds that transferred from central government to autonomous region proven to provide significant positive effect on human development index. (6) Economic growth provides significant positive effect on human development. (7) Public expenditure of autonomous regions provides significant positive effect on human development. (8) The decline in total poor population of autonomous region provide significant positive effect on human development. (9) In general decentralization funds policies have positive impacts on human development of each autonomous region counties and cities. Keywords: Fiscal Decentralization; Policy; Human Development. JEL Classifications: E6; O1